Creating Public Value Through Public-Private Partnerships in Technical and Vocational Education and Training in Egypt - Tajuddin, Aseel Amr (AUC Knowledge Fountain, 2026)
Technical and Vocational Education and Training (TVET) has emerged in the last decade as a foundational pillar for Egypt’s workforce and economic development vision. More recently, the Egyptian Ministry of Education and Technical Education (MoETE) has scaled industry driven and Public Private Partnerships (PPPs) TVET models, industry affiliated dual education programs and Applied Technology Schools (ATS), seeking to strengthen alignment with the labor market and improving TVET graduates employability. Yet, TVET in Egypt continues to suffer from persistent social stigma, limited social legitimacy and low social ranking, despite the state led reform efforts. Existing TVET literature remains limited to examining the Technical efficiency and performance dimensions of TVET systems, while factors influencing the societal recognition and acceptance such as public value, legitimacy and social perception remain unaddressed. Consequently, this study examines the under explored factors which shapes legitimacy formation, social perception and public value creation of the TVET pathways with Egypt, using Elsewedy Technical Academy and its affiliated Applied Technology Schools (ATS) as a substantive qualitative case. The study applies an interpretive qualitative approach theoretically informed by Behavioral Public Administration and Public Value Theory. Data collection was conducted through in depth semi structured interviews with stakeholders who are directly affiliated to STA including, students, graduates, parents, institutional representatives, employers, and policy makers. In addition to analysis of media materials, policy documents, social media and institutional communication materials. Research findings highlighted that legitimacy and social recognition of industry driven TVET models are mainly shaped by the interaction of three interdependent domains: Institutional Excellence, Industry Verification, and Strategic Communication collectively interacting together to shape the social perception and public value of TVET pathways in Egypt. Moreover, findings revealed that strong institutional performance and industry alignment do not automatically translate into broader social recognition. Drawing on these findings, this research suggests a set of system and institutional level recommendations seeking to develop a more structured communication approach to bridge the gap between institutional quality and social recognition developed to improve TVET legitimacy and social perception within the Egyptian society. Consequently, this study contributes to the TVET literature by expanding the scope of Behavioral Public Administration and Public Value Theory into the of recognition and legitimacy formation within TVET contexts.